2021
DOI: 10.2139/ssrn.3813643
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Differential Impact of COVID-19 on Self-Employed Women and Men in the United Kingdom

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…The COVID-19 crisis confirms the significant impact of crowd wisdom, social consciousness, and collective knowledge formation. Darja Reuschke, et al (2021) found that COVID-19 impact self-employment exits were not gender-specific. But women are more likely to lose income due to depletion of working hours.…”
Section: Review Of Literaturementioning
confidence: 87%
“…The COVID-19 crisis confirms the significant impact of crowd wisdom, social consciousness, and collective knowledge formation. Darja Reuschke, et al (2021) found that COVID-19 impact self-employment exits were not gender-specific. But women are more likely to lose income due to depletion of working hours.…”
Section: Review Of Literaturementioning
confidence: 87%
“…Evidence from cross-country data sets has been documented by ANDE (2020b) and Facebook et al (2020). Additional evidence from country-level studies has been documented for Bangladesh (Jaim, 2021); India (ANDE, 2020a;Chawla et al, 2020); the United Kingdom (Reuschke et al, 2021); and the United States (Fairlie, 2020;Manolova et al, 2020;Bloom et al, 2021), among other settings. Many of these studies, however, especially those referring to developing countries, are either based on relatively small samples (typically covering a few hundred firms or even fewer), or use a sampling approach that is not well suited to draw inferences on a target population (Schneider, 2020).…”
Section: Related Literaturementioning
confidence: 98%
“…Women are more likely to be pushed rather than pulled into self-employment, or small business ownership, meaning that some women may go into entrepreneurship by necessity and not because it is the most attractive career opportunity (Pines et al, 2010). During the COVID-19 crisis, women entrepreneurs were more likely to be at risk of reduced hours and earnings than men due to increased childcare responsibilities during lockdowns and school closures (Reuschke et al, 2021). Also, despite of being hit harder in some domains, women-led businesses were less likely to receive public support (Torres et al, 2021).…”
Section: Gender and Entrepreneurshipmentioning
confidence: 99%
“…8 Women-led businesses were more severely affected by the COVID-19 crisis than men-led businesses due to the increased need for childcare in the home associated with lockdowns and school closures (Reuschke et al, 2021;Torres et al, 2021).…”
Section: Study Limitationsmentioning
confidence: 99%